O Conteúdo do direito à liberdade de expressão na jurisprudência do Supremo Tribunal Federal - BACELAR, Rafaela Gonçalves (Universidade Federal do Pará, 2022)
This dissertation aims to identify the content of the right to freedom of expression developed by the jurisprudence of the Brazilian Supreme Court, seeking to analyze, from the inductive method and the jurisprudence research of, its foundations, justifications, and limits to its exercise. Therefore, the research was divided into three chapters. In the first, we analyze the Supreme Court judgments on the right in question, which were grouped according to discourse categories, identifying the argumentative parameters adopted by its ministers and the judgment trends. In the second chapter, we point out the theoretical discussions that permeate freedom of expression, in order to verify its relationship with what has been developed in jurisprudence and, therefore, to identify the content of the law. From these premises, we identified a central argumentative frame of the Court, however, endowed with an abstract and generic character, allowing the existence of decisions with divergences between the ministers. Finally, in the last chapter, we analyze the existence of external and internal factors that can influence the decision making posture of the Supreme Court and, thereby, the jurisprudential construction on freedom of expression, indicating other investigative fields to complement the hypotheses found. In conclusion, we emphasize that, despite a central argumentative framework, there is interpretive flexibility in its decisions, allowing subsequent court cases to be resolved based on criteria different from their precedents, being possible the influence of other factors in the decisionmaking.